Prospects for the Development of Sago Home Industry ((Metroxylon sp) In Aketobololo Village, Central Oba District, Tidore Island City, North Maluku - Mirnawati Mahangiri; Nur Azizah HS; Abdul Aziz Ramli (Peneliti.net, 2023)
This study aims to look at the process of selecting raw materials, processing and marketing as well as formulating a strategy for the development of a sago home industry in the villages of Akedotilou and Aketobololo with an emphasis on the aspects of opportunities, weaknesses, threats and challenges that occur in these businesses. This study uses a qualitative method with a descriptive approach. Data analysis used is SWOT analysis. internal factors (strength) that have an influence on the relatively high level of importance: (1) the availability of Raw Materials with an average weight of 0.76, followed by (2) Capital has an average weight of six experts of 0.63 ; (3) the availability of labor with an average weight of 0.56; (4) selling price with an average weight of 0.48; (5) Skills with an average weight of 0.36. Internal factors (weaknesses) that have an influence on the relatively high level of importance: (1) Land Ownership with an average weight of 0.14, followed by (2) Packaging with an average weight of 0.12; (3) Promotion with an average weight of 0.07; (4) There is no Health Standard and BPOM with an average weight of 0.05. 3. external factors (opportunities) that have the highest relative influence or level: (1) strategic industrial position with an average weight of six packs of 0.84, followed by (2) demand for sago with an average weight of 0 .48; (3) socio-cultural conditions with an average weight of 0.39. The results of the evaluation of the EFE matrix, obtained a total score of 3.87 which indicates the business conditions for processing sago flour are moderate or above average. External factors (threats) that have the highest relative importance or influence: (1) business competition with an average weight of six experts of 0.84, followed by (2) natural conditions with an average weight of 0. 68; (3) there has been no government attention with an average weight of 0.36 (4) inadequate road conditions with an average weight of 0.28.